Role of stress risk in development and course of cerebrovascular pathology - Markova, Marianna; Yavorska, Tetiana (Psychosomatic Medicine and General Practice, 2018)
The aim of research was to evaluate peculiarities of the influence of stress risk factors (behavioral and psychoemotional) in patients with cerebrovascular pathology (CVP) in the dynamics of its development as targets of psychological help. Materials and methods. The study involved 122 patients with cardiovascular disease with high risk of development CVP – group 1 (G1), 134 patients with clinical manifestations of CVD in form of transient ischemic attacks (TIA) in history – group 2 (G2) and 127 patients who had an ischemic stroke (IS) – group 3 (G3). As a comparison group (CG) observed 47 conditionally healthy persons with no risk or signs of CVP, verified by clinical and laboratory studies. To study the potential stress factors, the Boston Stress Test used with a modification of scoring scales. Results A high level of stress in the G1-3 was diagnosed, which prognostically indicated about a significant risk for the development of somatic and psychic changes in patients with CVD (34,9±11,7 points in G1, 37,1±11,9 points in G2 and 37,4±12,0 points in G3, p=0,201), whereas in the CG the stress potential was lower (27,7±12,8 points). The correlation between behavioral and psychoemotional stress components showed that in patients with CVP was a higher level of behavioral stress-potentiating factors (18.0±6.1 points versus 17.0±6.1 points, p<0.001), and in patients with IS – psycho-emotional (16,8±5,1 points versus 20,6±7,42 points, p<0,001). While in persons with TIA and CG – in the formation of stress disorders acts the both behavioral and psycho-emotional components (18,3±6,2 and 18,8±6,3 points, p=0,095 in G2, 13,8±6,5 and 13,9±6,8 points, p=0,81). Conclusions. The higher level of stress, the influence of a wide range of stress-potentiating factors, especially psycho-emotional genesis, in patients with cardiovascular risk and CVD, suggest the need to developing, organizing and implementing psychological measures for this contingent of patients based on a health-centered approach.